Formalization of non-linear patterns of evolutionary ecosystem processes under anthropogenesis influence - Plyatsuk, Leonid; Chernish, Elizabeth (Eastern-European Journal of Enterprise Technologies, 2016)
The analysis of non-linear aspects of the kinetics of organic contaminants’ decomposition in an aquatic ecosystem has substantiated the destruction patterns for environmental pollutants with regard to the biotic component. The findings of studying transformations in oil fractions of porous matters concern a number of indicators that are related to the biotic component of the ecosystem and previously disregarded in the sample models. In particular, it concerns the extent of biodegradation, bioassimilation and biotoxication of the natural environment. The study has revealed that these indicators influence the quality of assessing the carrying capacity of an ecosystem. The developed formalized model of synergistic patterns in the evolution of species allows us to consider the reconstructive potential of the corresponding ecosystem and a possibility to assimilate all types of pollutants due to the genesis of species and their populations. This entails that the model includes bifurcation of genetic variability, which manifests itself through an autocatalysis process of mutations at different organisation levels of living organisms under the influence of external environmental factors (including determinism of resources and their quality). The study has disclosed a possibility of formalizing the living systems of different taxonomic ranks. The modelling accounted for the factors of self-regulation and autocatalysis at different organisation levels of the population and organisms.